A Systematic Literature Review on Progressive Web Application Practice and Challenges - Reza Fauzan; Ice Krisnahati; Bima Dinda Nurwibowo; Della Aulia Wibowo (IPTEK The Journal for Technology and Science, 2022)
This research aims to establish a knowledge of Progressive Web Application (PWA) method practices based on published empirical investigation, the problems that the PWA method may face, and the PWA method's approach to experimental studies. We also looked for PWA practices that might address the issues with the prior method. We performed a broad, automated search to find SLRs and 43 papers published from 1 January 2015 to 6 November 2021 that discuss PWA. Specific inclusion and exclusion criteria were applied to determine which relevant studies we used for our research purposes. The review identified 31 practices of PWA, Six challenges of the previous approach of mobile application development that get resolved by PWA, and seven challenges posed by the practice of PWA. PWA was introduced in 2015, and since 2017 the studies on PWA topics have started increasing. The distribution of studies based on nations is spread evenly. 74% of selected studies are about the practice of the PWA. Although it cannot be generalized that the PWA approach handles the challenge of the previous method, some studies reported that PWA covers the problems of the previous methods. However, despite its benefits, PWA still has some challenges, mostly related to browser support.